1964
DOI: 10.1063/1.1726358
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Pressures of the Rare-Earth Metals

Abstract: Vapor-pressure measurements on the rare-earth metals were made by the Knudsen effusion technique using a quartz-fiber microbalance over a pressure range of 10—1 to 10—4 mm of Hg. The material used was specially prepared in order to minimize impurity effects. Ytterbium is the most volatile of the rare-earth metals, while lanthanum and cerium are the least volatile. The data were fitted to a straight line by the least-squares method and the heats of vaporization or sublimation were calculated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

1966
1966
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(37 citation statements)
references
References 26 publications
3
33
0
1
Order By: Relevance
“…The ionization cross-sections of Y, Cu, and Ni [21] listed in Table 2 were also used for the calculation: Fig. 6 depicts the vapor pressures of Y obtained in this study, and compares them with those reported by Ackermann et al [10,12] and Habermann and Danne [11], and those calculated from the data of Barin and Knacke [9]. This figure indicates that the vapor pressures of Y measured by the four experimental runs showed almost the same value irrespective of the reference material and orifice size, providing evidence for the validity of our experimental method.…”
Section: Vapor Pressure Of Elemental Yttriummentioning
confidence: 99%
See 2 more Smart Citations
“…The ionization cross-sections of Y, Cu, and Ni [21] listed in Table 2 were also used for the calculation: Fig. 6 depicts the vapor pressures of Y obtained in this study, and compares them with those reported by Ackermann et al [10,12] and Habermann and Danne [11], and those calculated from the data of Barin and Knacke [9]. This figure indicates that the vapor pressures of Y measured by the four experimental runs showed almost the same value irrespective of the reference material and orifice size, providing evidence for the validity of our experimental method.…”
Section: Vapor Pressure Of Elemental Yttriummentioning
confidence: 99%
“…As for yttrium (Y), a few data on vaporization of elemental Y from 1336 to 2185 K [10][11][12] and activity of Y in the Y-O system at 2000 K were reported [12]. These were examined by using Knudsen effusion technique [11] and single Knudsen mass spectrometry [10,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The determined vapor pressures of La and Ce could be expressed as functions of temperature by the least-squares method as follows: ln ðP La =PaÞ ¼ 27:2 AE 1:7 À ð54; 000 AE 2; 500Þ 1 T ½6 ln ðP Ce =PaÞ ¼ 27:2 AE 0:8 À ð53; 600 AE 1; 300Þ 1 T ½7 Figure 7 compares the vapor pressures of Sc, La, and Ce determined in this study with those reported by Ackermann and Rauth [8] and Habermann and Danne. [9] As shown in the figure, the previous measurements were limited to a higher pressure range, whereas lower pressures were measured in this study. Our results are basically in agreement with the extrapolation value of their data for each substance, indicating that low vapor pressures on the order of 10 À4 to 10 À3 Pa could be accurately measured.…”
Section: B Experimental Proceduresmentioning
confidence: 99%
“…The Gibbs energies of formation of gaseous elements were derived from the vapor pressures. Ackermann and Rauth [8] and Habermann and Danne [9] reported on the vapor pressure measurements of these metals at high temperature (more than 1520 K for Sc and more than 1874 K for La and Ce). The thermodynamic properties of these metals in a wide range of temperature are listed in a book edited by Barin and Knaeke.…”
Section: Introductionmentioning
confidence: 99%